The agenda of political mistakes in the fictional work A mulher do prefeito - Fernandes, Carla Montuori (2015)
This articlediscusses the integration of thematic policies in teleplaywright, from the concept of Agenda-setting. Within the fictional narrative, its importance is enhanced mainly by the way the fictional genre incorporates social, political and economic events on the national scene and, from scheduling, reflectsissues already aired in journalism. Accordingly, the objectiveof this paper is to analyze the themes of the television serieA mulher do prefeito, producedby Globo, which crossed the border and were broadcast journalism in the plot. The analysis of the chapters will be supported in the typologycreatedby Weber and Souza (2009), in a study that describes the representation of political themes in major works fictional television.